Book review: Teachers and teaching in vocational and professional education - Papier, Joy [Verfasser] (My University, 2019)
"Loo's achievement in this monograph is a convincing illustration of the essential elements of a vocational/occupational teacher training curriculum, through careful empirical analysis of what occupational teachers in their practice rely on. In addition, the collective wisdom and scholarship garnered through the ages is acknowledged and built upon throughout the development of his argument. Second, the conceptualisation of occupational teachers' capacities (OTC) offers a holistic approach to training teachers that recognises and values their life and work experience. Several implications for policymakers, curriculum developers, and teacher educators are apparent from this study, but it will no doubt interest occupational teachers and their managers to reflect meta-cognitively on what it is that these teachers do, often implicitly, which this book illuminates." (Textauszug ; BIBB-Doku)
Keywords: P 3.2.3 Lehrer; I 2.2.1 Westeuropa; Berufsschullehrer; Lehrerbildung; Vereinigtes Königreich